Analysing the Relationship Between Immigrant Status and the Severity of Offending Behaviour in Terms of Individual and Contextual Factors - Fernández-Pacheco Alises, Gloria; Torres-Jiménez, Mercedes; Martins, Paula Cristina; Mendes, Silvia María Vale (Frontiers in Psychology, 2022)
(1) Background: Social inclusion is a context for both risk and protective factors of migrant youth delinquency. This study aims to shed light on the issue by comparing delinquency among native, first-generation and second-generation immigrant youths in Portugal, a country located in the south of Europe, an area where research in this field is still scarce; (2) Methods: The research is based on the International Self-Reported Delinquency (ISRD-3) dataset, which includes information on over 4,000 adolescents, who self-reported on their socio-demographic status, leisure activities, school and neighbourhood environment, family bonds and self-control; (3) Results: Nested Logistic Regression analyses showed that a young first-generation immigrant is twice as likely to commit a crime, with or without violence, as a young native born in Portugal. However, no differences were found regarding the prevalence of delinquency among second-generation immigrants and natives, which is likely due to the integration and cultural assimilation of the immigrant over time; (4) Conclusions: These findings have relevant policy implications and are useful for evidence-based interventions aimed at promoting migrant adolescent well-being and targeting host countries’ performance.